界面に垂直なき裂を有する傾斜機能圧電積層 厚板の非定常電気熱弾性応答 - 上田, 整; 岡田, 真幸; 仲上, 佳寿 (傾斜機能材料論文集, 2017)
Abstract In this paper, the fracture problem of a functionally graded piezoelectric material strip (FGPM strip) containing a crack perpendicular to the interface between an FGPM strip and a homogeneous layer is considered. The problem is solved for the laminate that is suddenly heated from the surface of the FGPM strip. The surface of the homogeneous layer is maintained at the initial temperature. The crack faces are supposed to be completely insulated. Material properties are assumed to be exponentially dependent on the distance from the interface. By using the Laplace and Fourier transforms, the thermo- electro-mechanical fracture problem is reduced to a singular integral equation, which is solved numerically. The stress intensity factors are computed and presented as a function of the normalized time, the nonhomogeneous and geometric parameters.